Brillouin-Raman fiber laser with switchable wavelength spacing based on Brillouin pump distribution - Al-Alimi, Abdulmoghni Ali Wazea; Cholan, Noran Azizan; Salam, Sameer; Mustapha Kamil, Yasmin; Mohamed Ahmed, Mahmoud Hazzaa; Mahdi, Mohd Adzir (Elsevier, 2021)
A switchable multi-wavelength Brillouin-Raman fiber laser (MW-BRFL) is presented in this work. The MW-BRFL consists of a full-open linear cavity in which dispersion compensating fiber is employed as the gain medium for Brillouin and Raman amplification. The switching operation for single- and double-wavelength spacing MW-BRFL can be implemented by controlling Brillouin pump (BP) power distribution and direction that enters the laser cavity via two fiber-entry points. This is achievable by optimizing the splitting ratio of an optical coupler and the initial BP power. For the proposed laser setup, a 30/70 optical coupler was found to be the optimum. By setting the initial BP power at −3.0 dBm, 246 laser lines with 20-GHz frequency spacing were observed. The transformation to 10-GHz frequency spacing was attained by increasing the BP power to 11.8 dBm that resulted in 483 laser lines. All the counted laser lines had 3 dB peak power variation and were spread across a 38 nm bandwidth. In a nutshell, the proposed MW-BRFL is promising with respect to its performance, simplicity and flexibility.